Inflammatory-Dependent Bidirectional Effect of Bile Acids on NLRP3 Inflammasome and Its Role in Ameliorating CPT-11-Induced Colitis - Liao, Chuyao; Wang, Di; Qin, Siyuan; Zhang, Ying; Chen, Jie; Xu, Ruijie; Xu, Fengguo; Zhang, Pei (Frontiers in Pharmacology, 2022)
Irinotecan (CPT-11) in combination with 5-fluorouracil and leucovorin is a first-line chemotherapy regimen for the treatment of colorectal cancer, however, its clinical application is limited by the dose-limiting gastrointestinal toxicity of colitis. In our previous studies, several bile acids (BA) were found significantly elevated in the colon of CPT-11-induced rat colitis model. On the other hand, NLRP3 inflammasome has been reported to play important roles in mediating colitis. Interestingly, BA was stated to activate the NLRP3 inflammasome in some studies, while in some other reports it showed an inhibitory effect. We assumed the inflammatory status in different circumstances might have contributed to the controversial findings. In this study, we first discovered under non-inflammatory conditions, that supplementing BA could activate the NLRP3 inflammasome in THP-1 differentiated macrophages and promoted inflammation. In lipopolysaccharide (LPS)-induced inflammatory macrophages, however, BA inhibited the NLRP3 inflammasome and reduced inflammation. Further experiments demonstrated that Takeda G protein–coupled receptor 5 (TGR5) is essential in mediating the inhibitory effect of BA while phospho-SP1 (p-SP1) is key to the activation. Furthermore, we applied the above findings to ameliorate CPT-11 caused colitis in rats by inhibiting SP1 with mithramycin A (MitA) or activating TGR5 using oleanolic acid (OA). Our findings may shed light on the discovery of effective interventions for reducing dose-limiting chemotherapy-induced colitis.